Pemahaman Hadis Majlis Ulama Indonesia (MUI): Telaah Atas Fatwa tentang Pemilu - Azam, Azam (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2020)
Abstract The existence of Majlis Ulama Indonesia is seen as very important amid the reality of the plurality of Indonesian Islamic society. The advancement and religiousness of Muslims in the realm of religious thought, social organization, tendencies of flow, and political aspirations not only being a strength but also often incarnates into weaknesses and sources of conflict among Muslims themselves. The Majlis Ulama Indonesia is to create good living conditions, society, nationality, and good national matters, towards a quality society and the realization of the glory of Islam and Muslims in the Unity Republic of Indonesia. The Majlis Ulama Indonesia is to create good living conditions, society, nationality, and good national matters, towards a quality society and the realization of the glory of Islam and Muslims in the Unity Republic of Indonesia. The phenomenon of elections is a contemporary problem faced by the Majlis Ulama Indonesia, in this case, there is not a normative text that is explicitly contained in the Qur'an or the Sunnah of the Prophet. Then it is necessary to take new steps to interconnect between historical-political texts in order to create dynamic dialogue, and then the decision of the Majlis Ulama Indonesia is obliged to participate in making elections, one of which is to choose a leader who is trustworthy and has skills in the field of leadership. Because considering the mafsadat and maslahat, thus participation in the election is an obligation to choose a leader who is considered beneficial, both for the common people, nation, and state. Keywords: Hadis, Majlis Ulama Indonesia, Fatwa, electoral Election. Abstrak Eksistensi Majlis Ulama Indonesia dipandang sangat penting di tengah realitas pluralitas masyarakat Islam Indonesia. Kemajmukan dan keagamaan umat Islam dalam alam fikiran keagamaan, organisasi sosial, dan kecendrungan aliran dan aspirasi politik selain dapat merupakan kekuatan, tapi juga sering menjelma menjadi kelemahan dan sumber pertentangan dikalangan umat Islam sendiri. Majlis Ulama Indonesia adalah tercipta kondisi kehidupan, kemasyarakatan, kebangsaan, dan kenegaraan yang baik, menuju masyarakat yang berkualitas dan terwujudnya kejayaan Islam dan kaum muslimin dalam negara Kesatuan Republik Indonesia. Fenomena pemilu merupakan problematika kontemporer yang dihadapi oleh Majlis Ulama Indonesia, dalam kasus ini tidak selalu ada teks normatif yang secara eksplisit terdapat dalam al-Qur’an maupun sunnah Nabi. Maka perlu menempuh langkah-langkah baru untuk menginterkoneksikan antara teks historis-politik agar tercipta dialogis yang dinamis, maka keputusan dari Majlis Ulama Indonesia wajib ikut serta untuk mengsuksekan pemilu, salah satunya adalah memilih pemimpin yang amanah dan punya skil dalam bidang kepemimpinan. Karena mempertimbangkan antara mafsadat dan maslahat, dengan demikian itu keikutsertaan dalam pilres adalah suatu kewajiban untuk memilih pemimpin yang dianggap bermaslahat, baik bagi umat, bangsa dan negara. Kata Kunci: Hadis, Majlis Ulama Indonesia, Fatwa, Pemilihan Umum.